Islamic heritage and civilizational reform: connecting the broken and raising the vanished / Zaid Ahmad - Ahmad, Zaid (Academy of Contemporary Islamic Studies (ACIS), 2021)
This keynote dwells on the issues of Islamic heritage in connection with the need for civilizational reform. As historically recorded, Islam had once achieved the plethora of civilization which was often metaphorically described as the golden era. The golden era (al- ‘asr al-dhahabi) - stretched approximately between 8th to 14th century Islam, had witnessed the flourishing of knowledge, arts, culture and scientific traditions. The establishment of the House of Wisdom in Baghdad (Bayt al-Hikmah) had not only gathered scholars and scientist among Muslim, but also attracted scholars and polymaths from different background coming from various parts of the world. The Muslim scholars had shown a desirous interest in adapting and integrating knowledge and scientific traditions from other civilisations, hence greatly enriched the treasure of Islamic heritage. Classical works from other languages - Greeks, Persians and other traditions were translated and made available in Arabic. Nevertheless, the subsequent of a series of colonization, the academic and intellectual traditions that had been established had ceased to continue. The continuity of the Islamic tradition had been disrupted and taken over by the colonial traditions. The hiatus that took place in the colonised Muslim societies had resulted in the broken chain of the tradition and the gradual vanishing of the valuable heritage of the past. This situation had subsequently left a sort of lacuna in Islamic intellectual tradition. When the colonials stepped into the Muslim lands, they had brought together their influence in culture, intellectual and scientific traditions as well as in their value systems. Colonisation that took place in the Muslim societies had paved the way to broadening of the colonial knowledge and traditions. These influences had not only stagnated the continuity of the earlier tradition but had also corrupted them with their doctrines and ideologies. This condition had led to a secular system of education i.e. religious texts against the other sciences. This situation demands a well-ordered methodical call for a wide-ranging reform within Muslim societies. This civilizational reform must be holistic, all-inclusive and involve all aspects and facets of human life. This movement is important to connect the broken legacy and tradition of the past and to rase the vanished heritage of the past. Why do we need a civilizational reform? I refer to the framework of “sanad” (continuity) proposed by Ibn Khaldun (1332-1406). In order to sustain the achievement of a civilization, there must be a continuity in intergenerational knowledge transmission through education. It is in the same line of argument; I propose a framework of civilization reform as the way forward to bring back the great legacy of Islamic heritage. This can be realised through a wide range of intellectual, academic, social, cultural and political movement that would lead the path. This movement should start with reform in knowledge and scientific tradition. Two processes must concurrently take place namely 1) decolonisation and 2) Islamization/indigenization. The question whether Islamic heritage once again can play a catalytic role depends on how far the broken link can be connected and how much the vanished heritage can be placed in the civilizational mainstreams.